ATTAINING THE EQUITABLE DISTRIBUTION OF TEACHERS IN UNDERDEVELOPED REGIONS AT WEST KALIMANTAN PROVINCE - Andina Nurul Wahidah (ICoTE Proceedings)
This study aims at describing the distribution conditions of teachers and principals in underdeveloped regions, examine the impact of distribution conditions to the students partisipation number in education, and identifying the root causes of inequitable distribution to attaining the equitable distribution of teachers. The researchers used  the data collected for junior high school students in underdeveloped regions at West Kalimantan Province. The data obtained from Data Center of Education and Culture Statistics, Ministry of Education and Culture Republic of Indonesia in 2016. The findings proved that inequitable distribution of teachers in underdeveloped regions is still happen. It can considered has negative impact to students partisipation number of education. Therefore, requires synergy of roles of principals, district leaders and state leaders to solve it. Overall, this study provides critiques and suggestions to complete the strategic actions in attaining the equitable distributions of teachers in underdeveloped regions at West Kalimantan Province, Indonesia.